The identification of novel immunogenic antigens as potential Shigella vaccine components - de Alwis, R; Liang, L; Taghavian, O; Werner, E; The, HC; Thu, TNH; Duong, VT; Davies, DH; Felgner, PL; Baker, S (BioMed Central, 2021)
Background Shigella is a major diarrheal pathogen for which there is presently no vaccine. Whole genome sequencing provides the ability to predict and derive novel antigens for use as vaccines. Here, we aimed to identify novel immunogenic Shigella antigens that could serve as Shigella vaccine candidates, either alone, or when conjugated to Shigella O-antigen.